2018
DOI: 10.1093/nar/gky546
|View full text |Cite
|
Sign up to set email alerts
|

The sequence features that define efficient and specific hAGO2-dependent miRNA silencing guides

Abstract: MicroRNAs (miRNAs) are ribonucleic acids (RNAs) of ∼21 nucleotides that interfere with the translation of messenger RNAs (mRNAs) and play significant roles in development and diseases. In bilaterian animals, the specificity of miRNA targeting is determined by sequence complementarity involving the seed. However, the role of the remaining nucleotides (non-seed) is only vaguely defined, impacting negatively on our ability to efficiently use miRNAs exogenously to control gene expression. Here, using reporter assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Additionally, single molecule studies have demonstrated the importance of the seed in stable target site engagement [11][12][13]. Interestingly, once miRISC binds target RNA, AGO can undergo a conformational change that allows for extended seed pairing and exposes part of the miRNA 3' region (nts [13][14][15][16] for additional interactions with the target [14]. A recent systematic investigation of pairing interactions between a miRNA and target corroborates a sequential recognition model where the miRNA seed binds first and then nts in the 3' half are able to bind the target site [15].…”
Section: Target Recognition and Regulation By Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, single molecule studies have demonstrated the importance of the seed in stable target site engagement [11][12][13]. Interestingly, once miRISC binds target RNA, AGO can undergo a conformational change that allows for extended seed pairing and exposes part of the miRNA 3' region (nts [13][14][15][16] for additional interactions with the target [14]. A recent systematic investigation of pairing interactions between a miRNA and target corroborates a sequential recognition model where the miRNA seed binds first and then nts in the 3' half are able to bind the target site [15].…”
Section: Target Recognition and Regulation By Mirnasmentioning
confidence: 99%
“…Interestingly, once miRISC binds target RNA, AGO can undergo a conformational change that allows for extended seed pairing and exposes part of the miRNA 3' region (nts [13][14][15][16] for additional interactions with the target [14]. A recent systematic investigation of pairing interactions between a miRNA and target corroborates a sequential recognition model where the miRNA seed binds first and then nts in the 3' half are able to bind the target site [15]. The relevance of pairing to miRNA 3'-end sequences has been demonstrated in several new studies showing that it can impact the specificity of targeting, the regulatory mechanism, and the stability of the miRNA itself.…”
Section: Target Recognition and Regulation By Mirnasmentioning
confidence: 99%
“…3′UTR sequence for human gene annotated as protein coding were obtained from Ensembl release 104 using BioMart sequence of the miRNA. 39,40 The vast majority (98%) of all RefSeq annotated genes are considered potential targets of miRNAs. 41…”
Section: Mirnasmentioning
confidence: 99%
“… 38 Furthermore, additional pairing can occur with the 3′ end sequence of the miRNA. 39 , 40 The vast majority (98%) of all RefSeq annotated genes are considered potential targets of miRNAs. 41 miRNAs have been reported to interact with coding sequences (CDS), with 5′UTRs, intronic regions and 3′UTRs of their target mRNA.…”
Section: Sequences and Structural Motifs As Hubs For Post‐transcripti...mentioning
confidence: 99%
“…In particular, targeting is dependent upon the base pairing of the seed region, nucleotides (nts) 2-7 of the miRNA to sites in mRNA 3 UTRs. In addition, the 3 end of the miRNAs has also been found to be involved in regulating the target specificity and regulation [76], where the extent of base-pairing to the miRNA 3 -end can influence the stability of the miRNA itself, and this signifies the importance of miRNA sequence beyond the seed region [75]. Thus, we believe the sequence of miRNA itself has a pivotal role in the whole process of regulation of the gene expression.…”
Section: Discussionmentioning
confidence: 89%